Library collections in the life of the user: two directions - Lorcan Dempsey (Liber Quarterly: The Journal of European Research Libraries, 2016)
The paper considers how the changing nature of research in digital environments is reshaping the nature of library collections and services in academic and research libraries. It describes two central directions, each a response to the centrality of the user in a network environment. First, the library has an increasing role in managing the research and other outputs of the university (the inside-out collection). Second, the library is facilitating access to a broader range of local, external and collaborative resources organized around user needs (the facilitated collection).